2021
DOI: 10.1177/02841851211003289
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided transperineal laser ablation for percutaneous treatment of benign prostatic hyperplasia: a new minimally invasive interventional therapy

Abstract: Background Although there are different treatments for benign prostate hyperplasia, their efficacy and safety differ. We are currently exploring a new minimally invasive interventional therapy for benign prostatic hyperplasia (BPH). Purpose To determine the feasibility, effectiveness, and safety of ultrasound-guided transperineal laser ablation (US-TPLA) for the treatment of BPH. Material and Methods Twenty patients with BPH (mean age = 73.9 ± 9.2 years) who underwent US-TPLA from June 2018 to January 2020 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(59 citation statements)
references
References 23 publications
(16 reference statements)
3
42
0
Order By: Relevance
“…Using very thin applicators and high-precision energy delivery, percutaneous laser ablation has been demonstrated to be safe and effective ( 45 48 ). Several preliminary studies including short-term follow-up proved its feasibility, Pacella revealed IPSS improved from 22.5 ± 5.1 to 7.7 ± 3.3 at 6 months and 7.0 ± 2.9 at 12 months, Cai HJ proved ultrasound guided TPLA effective and safe with the QoL improved from 4.9 ± 1.7 to 2.3 ± 1.3 and the Qmax improved from 8.5 ± 3.0 to 15.2 ± 4.8 mL/s at 6 months after the procedure ( 37 , 41 ). However, no comparison with patients treated with other techniques has been performed, especially TURP, the most widely used surgical method and “gold standard” for BPH patients.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Using very thin applicators and high-precision energy delivery, percutaneous laser ablation has been demonstrated to be safe and effective ( 45 48 ). Several preliminary studies including short-term follow-up proved its feasibility, Pacella revealed IPSS improved from 22.5 ± 5.1 to 7.7 ± 3.3 at 6 months and 7.0 ± 2.9 at 12 months, Cai HJ proved ultrasound guided TPLA effective and safe with the QoL improved from 4.9 ± 1.7 to 2.3 ± 1.3 and the Qmax improved from 8.5 ± 3.0 to 15.2 ± 4.8 mL/s at 6 months after the procedure ( 37 , 41 ). However, no comparison with patients treated with other techniques has been performed, especially TURP, the most widely used surgical method and “gold standard” for BPH patients.…”
Section: Discussionmentioning
confidence: 89%
“…Can laser treatment of prostate guided by TRUS achieve the minimally invasive treatment of BPH using a percutaneous transperineal approach? Researchers have verified transperineal percutaneous laser ablation (TPLA) a feasible and safe method (35)(36)(37)(38)(39)(40). Pacella CM conducted a single arm trial, performed the analysis on 160 patients with 6 months follow and 83 patients with 12 months after TPLA (41), and de Rienzo G conducted TPLA for 21 patients, verified the significant advantage in Qmax, IPSS, and peculiar ability to preserve ejaculation (38).…”
Section: Introductionmentioning
confidence: 99%
“…Of note, none of the available systematic reviews in this field included data from TPLA, though different authors have already described its feasibility and safety in real-life settings (7)(8)(9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the clinical improvements reported with this technique might theoretically be still inferior to those obtained by recommended techniques such as TURP and enucleative procedures, especially from a pure urodynamic standpoint. On the other side, TPLA has several potential advantages over traditional techniques, including avoidance of general anesthesia, performance in an outpatient setting, the low risk of intra-and perioperative adverse events and the virtually absent risk of ejaculatory disfunction (3,(7)(8)(9)(10)(11)(12). In this regard, the right placement of the applicators and the use of the planning software of Echolaser Smart Interface during TPLA is crucial to maintain a safe distance from the bladder neck and the urethral lumen (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation